Influence of body weight measurement frequency on the bone health of female athletes - Tsukahara, Y.; Kuribayashi, C.; Akiyama, E. (Research Quarterly for Exercise and Sport, 2025)
Purpose: Athletes struggle with bone stress injuries despite the many risk factors reported in previous studies. However, the relationship between body weight measurement frequency and risk of stress fractures has yet to be investigated. Thus, the purpose of this study is to seek the link between body weight measurement frequency and the occurrence of stress fractures.